2014
DOI: 10.4317/medoral.19536
|View full text |Cite
|
Sign up to set email alerts
|

Single-blind randomized clinical trial to evaluate clinical and radiological outcomes after one year of immediate versus delayed implant placement supporting full-arch prostheses

Abstract: Purpose: To evaluate and compare peri-implant health, marginal bone loss and success of immediate and delayed implant placement for rehabilitation with full-arch fixed prostheses. Material and Methods: The present study was a prospective, randomized, single-blind, clinical preliminary trial. Patients were randomized into two treatment groups. In Group A implants were placed immediately post-extraction and in Group B six months after extraction. The following control time-points were established: one week, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…In general, there are many interacting factors that would affect the success of IL implants such as bone quality and quantity, clinician skill and experience, implant design, implant primary stability, macro‐ and micromovements, and occlusion 35 . Previous results indicated IL achieved a similar high success rate to that noted in the conventional approach (delayed protocols) 5 , 8 , 36 . This conclusion is in accordance with the present findings, where no significant differences were found between IL and DL within smokers and non‐smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there are many interacting factors that would affect the success of IL implants such as bone quality and quantity, clinician skill and experience, implant design, implant primary stability, macro‐ and micromovements, and occlusion 35 . Previous results indicated IL achieved a similar high success rate to that noted in the conventional approach (delayed protocols) 5 , 8 , 36 . This conclusion is in accordance with the present findings, where no significant differences were found between IL and DL within smokers and non‐smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to advancements in oral implantology, such as implant design and titanium surface treatment, the immediate loading (IL) concept has gained popularity by offering shortened treatment time, trauma reduction, decreased patient anxiety and discomfort, and improvement in function and esthetics 3–5 . Several studies 6–8 have reported similar success rates, implant survival, and crestal bone loss (CBL) between delayed loading (DL) and IL of implants. Several factors, such as poorly controlled diabetes mellitus (DM), poor bone quantity and/or quality, and smoking, have been reported to negatively influence success and survival rates of implants 9 , 10 …”
mentioning
confidence: 99%
“…Most of the selected studies evaluated implants that had been inserted in maxilla 8,10,23,25,29,32,36,39,[41][42][43][44][45]47 , and both dental arches 22,26,28,30,31,34,35,37,40,46,48 , involved the anterior and posterior regions. Fourteen studies included patients who smoked 10,24,[26][27][28][29][30][33][34][35]38,[46][47][48] and five studies included patients with periodontal compromised status 27,28,31,40,46 .…”
Section: Demographic Datamentioning
confidence: 99%
“…3A). However, Fresh sockets versus healed sockets 1149 46 Longitudinal case control study 48 Prospective, randomized clinical study 23 Immediate Y N/N N N Y/-Colomina 24 Immediate N Y/N N N Y/Y Cooper et al 25 Immediate N N/N N NR NR Davarpanah et al 26 Immediate and Delayed Y Y/N N 1 (Imed) NR De Bruyn and Collaert 27 Immediate and Delayed N Y/N Y Y N/Y Deng et al 28 Immediate N Y/N Y NR Y/Y Esposito et al 29 Immediate or Delayed Y Y/N N N Y/Y Grandi et al 10 Immediate Y Y/N N NR Y/Y Han et al 30 Immediate Y Y/N NR N Y/Y Jo et al 31 Immediate and Delayed N NR Y N NR Kan et al 32 Immediate Y N/N N NR Y/Y Krennmair et al 33 Immediate N Y/N N NR Y/Y Lindeboom et al 8 Non-loaded Y N/N N NR Y/Y Luongo et al 34 Immediate Y Y/N N N Y/Y Oxby et al 35 14-53 days N Y/N N N Y/-Palattella et al 36 Immediate N N/N N NR Y/Y Pellicer-Chover et al 37 12 weeks (Max) 10 weeks (Mand) 43 Immediate N N/N N NR Y/Y Rieder et al 44 Immediate and Delayed Y N/N N N N/Y Siciliano et al 45 -N N/N N N Y/Y Siebers et al 46 4-6 months N Y/N Y NR NR Tsirlis 47 Delayed Y Y/N N N N/N van Kesteren et al 48 No prosthesis Y Y/N N NR NR Y = yes; N = no; NR = not reported. type 1 showed significantly higher failures rates when compared with type 3 (p = .005; RR 5.25, 1.67-16.49) ( Fig.…”
Section: Implant Survival and Complication Ratesmentioning
confidence: 99%
“…Although several clinical trials have showed high success rates for immediate restoration/loading over 6 years of follow‐up, a clinical dilemma regarding the loading protocol remains. It is still unknown whether dental implants should be immediately loaded or if it is a conventional loading protocol should be followed for more consistent outcomes . The immediate restoration/loading protocol has many advantages such as quicker achievement of occlusal function, early restoration of esthetic appearance, avoidance of a second surgery to expose the implant, and an increase in the percentage of transverse collagen fibers .…”
mentioning
confidence: 99%